Beyond standard English: how Global Englishes enhances creativity, reduces language anxiety, and increases willingness to communicate - Budiman, Asep; Liu, Xinyu (Frontiers in Psychology, 2025)
This article explores how the Global Englishes Language Teaching (GELT) paradigm promotes learner psychology by enhancing creativity, reducing language anxiety, and increasing willingness to communicate (WTC) in second or foreign language (L2) contexts. Drawing on key psychological and pedagogical theories alongside empirical research, the article argues that GELT offers a transformative alternative to traditional English language teaching (ELT) by validating diverse English varieties, reframing errors as communicative resources, and fostering learner agency. Through an interdisciplinary synthesis, the study demonstrates how GELT aligns with dynamic, learner-centered approaches to second language acquisition (SLA), enabling learners to express themselves more authentically, confidently, and creatively. The findings suggest that embracing Global Englishes not only supports linguistic competence but also nurtures emotional well-being and communicative autonomy, offering valuable insights for teachers, curriculum designers, and policymakers in today’s increasingly multilingual educational contexts.